Open-source geospatial technologies for census data mapping and visualization: The Romanian 2021 census - Andi M. LAZĂR; Florin IOSUB; Daniel URDĂ; Marius BUDILEANU (Nova Geodesia)
Romania conducted in 2022 the Population and Housing Census – with the 1st of December 2021 as reference date. Starting from 2023, the National Institute of Statistics (INS) began publishing the results. This contribution presents a methodological approach for transforming census parameters originally published as Excel tables into geospatial datasets. The process was carried out using open-source geospatial technologies. The datasets released by INS were analyzed, standardized, and then transformed into geospatial data using specific techniques, with results reported at both the county (NUTS 3) and Local Administrative Unit (LAU) levels. A key innovation of this study is the integration of the 1 km² population grid produced by EUROSTAT, to which we added 13 statistical parameters derived from the census data. The resulting datasets are stored in a PostgreSQL/PostGIS database and served through GeoServer, enabling the development of interactive web applications using MapStore. As part of this study, three interactive applications and two dynamic dashboards were created. The newly generated data is published under an open-source license, and can be viewed and analyzed online, accessed via standard web services, or downloaded for further use. By aligning the census results with the EUROSTAT 1 km² population grid, this article offers a new perspective on demographic data, allowing for in-depth analysis of population dynamics even at the level of cities and counties.